A Probit Analysis of the Incidence of the Cotton Leaf Curl Virus in Punjab, Pakistan (The Pakistan Development Review, 1997)
Factors affecting the incidence of the cotton leaf curl virus (CLCV) in Punjab, Pakistan are investigated using a probit model. The results indicate that the history of a cotton variety grown on the farm, better land preparation before sowing, and use of pesticides and phosphorus fertiliser significantly reduce the probability of incidence of the CLCV disease. The farmers having greater areas under cotton are less likely to be affected by the disease. Fields of the more experienced farmers, who have greater years of formal education, are also less likely to be affected, because these farmers are believed to be better managers. However, the probability of damage was positively related to age of the farmer, which implies that the aged farmers have less managerial capabilities. The intensity of the disease varied from district to district and also from variety to variety. Use of greater amounts of nitrogenous fertiliser, more severe insect attacks, and late sowing of the cotton crop significantly increase the incidence of the CLCV disease.